2017
DOI: 10.26773/smj.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Standing Height and its Estimation Utilizing Foot Length Measurements in Adolescents from Western Region in Kosovo

Abstract: A B S T R A C T The purpose of this research is to examine standing height in both Kosovan genders in the Western

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 15 publications
2
28
0
12
Order By: Relevance
“…It is interesting that a signifi cant number of research presentations at scientifi c conferences were not found in the subject search, especially when presentations at the annual scientifi c conferences organized in Serbia, Slovenia, Croatia and Montenegro are taken into account (Bjelica, Popovic, & Akpinar, 2014;2017) but it was confi rmed that all these researches that have been found (Popović, Bjelica, Petković, Muratović, & Georgiev, 2014;Popović, Milašinović, Matić, Gardašević, & Bjelica, 2016;Popović, Milašinović, Jakšić, Vasiljević, & Bjelica, 2016;Milašinović, Popović, Bjelica, & Vasiljević, 2016;Popović, Bjelica, Milašinović, Gardašević, & Rašidagić, 2016;, have later been published in magazines in full text, so that the subject analysis did not lose signifi cance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting that a signifi cant number of research presentations at scientifi c conferences were not found in the subject search, especially when presentations at the annual scientifi c conferences organized in Serbia, Slovenia, Croatia and Montenegro are taken into account (Bjelica, Popovic, & Akpinar, 2014;2017) but it was confi rmed that all these researches that have been found (Popović, Bjelica, Petković, Muratović, & Georgiev, 2014;Popović, Milašinović, Matić, Gardašević, & Bjelica, 2016;Popović, Milašinović, Jakšić, Vasiljević, & Bjelica, 2016;Milašinović, Popović, Bjelica, & Vasiljević, 2016;Popović, Bjelica, Milašinović, Gardašević, & Rašidagić, 2016;, have later been published in magazines in full text, so that the subject analysis did not lose signifi cance.…”
Section: Resultsmentioning
confidence: 99%
“…A signifi cant number of studies have indicated the usefulness of diff erent body parameters in assessing relative body height , Popovic, Gardasevic, Masanovic, Arifi , & Bjelica, 2017b and it was found that arm span was the most reliable of all of them (Jalzem, & Gledhill, 1993;Mohanty et al, 2001;Ter Goon et al, 2011), while foot length measurement is the most reliable predictor during adolescent age, due to the fact that ossifi cation and maturation occur earlier in the foot than the long bones and standing height could be more accurately predicted from foot measurement as compared to long bones during adolescent age (Singh, Kumar, Chavali, & Harish, 2012). On the other hand, it is widely known that body height and body proportions are specifi c when talking about populations living on Dinaroids.…”
Section: Introductionmentioning
confidence: 99%
“…Tako, istraživanja koja su se sprovela na teritoriji Kosova ukazuju da dužina tibije, dužina stopala, stojeća i sjedjeća visina imaju prediktivnu vrijednost kada je u pitanju tjelesna visina, ali ne tako pouzdanu kao što je to kod raspona ruku (Gardašević, 2018;Gardasevic, Masanovic, Arifi , 2018a;Gardasevic, Masanovic, Arifi , 2018b;Gardasevic, Masanovic, Arifi , 2018c;Masanovic, 2018c;Masanovic, Gardasevic, & Arifi , 2018d;Masanovic, Gardasevic, & Arifi , 2018e;Masanovic, Gardasevic, & Arifi , 2018f;Masanovic, Gardasevic, & Arifi , 2018g;Popovic, Arifi , & Bjelica, 2017a;Popovic, & Bjelica, 2017;Popovic, Gardasevic, Masanovic, Arifi , & Bjelica, 2017b;Masanovic, 2018b;Gardašević, 2018b;Masanovic, 2018a;Masanovic, Gardasevic, & Arifi , 2018a;Masanovic, Gardasevic, & Arifi , 2018b;Masanovic, Gardasevic, & Arifi , 2018c;). Ono što je očigledno jeste da odnos dugih kostiju i visine varira u različitim etničkim grupama (Bjelica i sar., 2012;Brown, Feng, & Knapp, 2002;Gardasevic i sar., 2018c ;Popovic, Bjelica, Tanase, & Milasinovic, 2015;Popović, Bjelica, Petković, Muratović, & Georgiev, 2014;Popović, Bjelica, Milašinović, Gardašević, & Rašidagić, 2016;Reeves, Varakamin, & Henri, 1996;Steele, & Chenier, 1990), kao i različitim regionima (Arifi , 2017a; Arifi , Bjelica, Sermaxhaj, Gardasevic, Kezunovic, & Popovic, 2017b;Popovic,2016).…”
Section: Diskusijamentioning
confidence: 99%
“…Sport Science,10(1), 92-5. Arifi , F., Bjelica, D., Sermaxhaj, S., Gardasevic, J., Kezunovic, M., & Popovic, S. (2017b …”
mentioning
confidence: 99%
“…BODY HEIGHT AND ITS ESTIMATION UTILIZING ARM SPAN | M. BUBANJA sanovic, Arifi , Bjelica, 2017b;. Visoki ljudi mogu imati veću dugovječnost, te imati manji rizik kardiovaskularnih i respiratornih bolesti, ali mogu imati veći rizik od nekih vrsta karcinoma (Quanjer i saradnici, 2014).…”
unclassified